Characterization of cissus quadrangularis fiber polymer composites along with properties analysis - Sankarasubramanian M; Pitchipoo P (Materials Research Express, 2021)
The natural fibers such as coir, flax, oil palm, jute etc are widely used in civil construction and automobile industries based on their advantages like eco friendlyness as well as their enhanced performances whereas the synthetic fibers namely kevlar, carbon and glass yield higher production costs. Hence in this present work, a new natural fiber, the Cissus Quadrangularis , which is made from the Cissus Quadrangularis plant, has been introduced and it is bio-degradable, renewable, and eco friendly. The chemical composition, density, mechanical properties and water absorption potential of fiber bundles are investigated and impressive results are obtained. The composite material has been fabricated by the fiber with different weight percentage in the form of powder and its characterizations and the mechanical properties have been studied. The results reveal that the fabricated composite is suitable for structural applications and a better replacement of synthetic fibers. The mechanical features of Cissus Quadrangularis are reinforced with unsaturated polyester composite and it is optimized by changing the fiber content.